Characterization of Functional Groups in Estuarine Dissolved Organic Matter by DNP‐enhanced 15N and 13C Solid‐State NMR. Issue 18 (19th August 2021) - Venel, Florian; Nagashima, Hiroki; Rankin, Andrew G. M.; Anquetil, Christelle; Klimavicius, Vytautas; Gutmann, Torsten; Buntkowsky, Gerd; Derenne, Sylvie; Lafon, Olivier; Huguet, Arnaud; Pourpoint, Frédérique
Abstract: Estuaries are key ecosystems with unique biodiversity and are of high economic importance. Along the estuaries, variations in environmental parameters, such as salinity and light penetration, can modify the characteristics of dissolved organic matter (DOM). Nevertheless, there is still limited information about the atomic‐level transformations of DOM in this ecosystem. Solid‐state NMR spectroscopy provides unique insights into the nature of functional groups in DOM. A major limitation of this technique is its lack of sensivity, which results in experimental time of tens of hours for the acquisition of 13 C NMR spectra and generally precludes the observation of 15 N nuclei for DOM. We show here how the sensitivity of solid‐state NMR experiments on DOM of Seine estuary can be enhanced using dynamic nuclear polarization (DNP) under magic‐angle spinning. This technique allows the acquisition of 13 C NMR spectra of these samples in few minutes, instead of hours for conventional solid‐state NMR. Both conventional and DNP‐enhanced 13 C NMR spectra indicate that the 13 C local environments in DOM are not strongly modified along the Seine estuary. Furthermore, the sensitivity gain provided by the DNP allows the detection of 15 N NMR signal of DOM, in spite of the low nitrogen content. These spectra reveal that the majority of nitrogen is in the amide form in these DOM samples and show an increased disorder around these amide groups near the mouth of the Seine. Abstract : Magical Magic‐angle spinning ! The aquatic ecosystems in estuaries are strongly affected by chemical and structural compositions of dissolved organic matter (DOM). Using 13 C and 15 N NMR enhanced by dynamic nuclear polarization, it is shown that the functional groups of DOM and their relative amounts are unmodified along the Seine estuary. Furthermore, most of the nitrogen atoms in DOM are in the amide form, even if they exhibit a larger distribution of local environments near the mouth of the Seine.